Knowledge, attitudes, and breastfeeding practices of postnatal mothers in a tertiary health center - Basavaraj Bheeman; H S Leena; K Pushpalatha (Indian Journal of Child Health, 2021)
Background: Breastfeeding has several benefits for both the infants and mothers. Despite strong evidences supporting breastfeeding, its prevalence has remained low worldwide. Objective: The objective of the study was to examine the knowledge and attitude toward breastfeeding and infant feeding practices among the Indian postnatal mothers. Materials and Methods: A cross-sectional descriptive study was carried out among randomly selected postnatal mothers at pediatric outpatient department at a tertiary care center. Data were collected by face-to-face interview using a structured questionnaire. Results: Our study showed that a majority of mothers (92%) of mothers were breastfeeders. However, 72% of the mothers were exclusive breastfeeders and 74% of mothers initiated breastfeeding within an hour. While mothers had good knowledge on breastfeeding (11.45±3.45), the average score of the Iowa Infant Feeding Scale (60.45±4.75) indicates neutral attitudes toward breastfeeding. Conclusion: Our findings show that though the frequency of exclusive breastfeeding was high compared to other studies, the gap should be filled. Thus, it is important to provide prenatal education to mothers on breastfeeding. We also recommend strengthening the public health education campaigns to promote breastfeeding.